Research on function model of lime-improved high liquid limit soil strength characteristics - Hongkun HU; Zhushan SHAO (Zhongguo dizhi zaihai yu fangzhi xuebao, 2021)
In view of the large number of high liquid limit soil abandonment problems along the roadbed of the Liyu Expressway in Guangxi, quick lime was used to improve the high-liquid limit soil. the high-liquid limit soil samples with different initial water content and different lime content from the spoil field were used to conduct lateral compression test and fast shear test, and the basic elementary mathematical function model was used to fit different saturation states and different initial water content. The effect of lower lime content on the compression characteristics and shear strength of the specimen is tested. The results show that: (1) The compression coefficient of high liquid limit soil decreases exponentially with the increase of lime content; (2) the cohesion and internal friction angle of the specimens in different saturated states change with the increase of lime content in the form of quadratic function; (3) High liquid limit soil has water sensitivity. The moisture content corresponding to the shear strength is 3%～6% higher than the moisture content corresponding to the maximum dry density of the compaction test; (4) When the initial moisture content is lower than 26.73%, it is recommended that the lime content is not less than 6%, otherwise the lime content of the modified high liquid limit soil is not less than 8%, which can be achieved under the premise of meeting economics and better improvement effect.